Design and Methods of a Participatory Healthy Eating Intervention for Indigenous Children: The FRESH Study - Blue Bird Jernigan, Valarie; Taniguchi, Tori; Haslam, Alyson; Williams, Mary B.; Maudrie, Tara L.; Nikolaus, Cassandra J.; Wetherill, Marianna S.; Jacob, Tvli; Love, Charlotte V.; Sisson, Susan (Frontiers in Public Health, 2022)
Objective: To increase vegetable and fruit intake, reduce body mass index (BMI), and improve parental blood pressure among American Indian families. Design: Randomized, wait-list controlled trial testing a multi-level (environmental, community, family, and individual) multi-component intervention with data collection at baseline and 6 months post-intervention. Setting: Tribally owned and operated Early Childhood Education (ECE) programs in the Osage Nation reservation in Oklahoma. Participants: American Indian families (at least one adult and one child in a ECE program). A sample size of 168 per group will provide power to detect differences in fruit and vegetable intake. Intervention: The 6-month intervention consisted of a 1) ECE-based nutrition and gardening curriculum; nutrition education and food sovereignty curriculum for adults; and 3) ECE program menu modifications. Main Outcome Measures: The primary outcome is increase in fruit and vegetable intake, assessed with a 24-hour recall for adults and plate weight assessments for children. Secondary outcomes included objective measures of BMI among adults and children and blood pressure among adults. Clinical Trials Unique Identifier: NCT03251950 (https://clinicaltrials.gov/ct2/show/NCT03251950)